Pain science education concepts for pelvic pain: an e-Delphi of expert clinicians - Amelia K. Mardon; Amelia K. Mardon; Amelia K. Mardon; Hayley B. Leake; Hayley B. Leake; Monique V. Wilson; Monique V. Wilson; Emma L. Karran; Emma L. Karran; Romy Parker; Romy Parker; Rinkle Malani; et al. (Frontiers in Pain Research)
IntroductionPersistent pelvic pain is a prevalent condition that negatively impacts one's physical, psychological, social, and sexual wellbeing. Pain science education (PSE) involves learning about the biology of pain and is commonly integrated into the management of persistent pain. However, PSE is yet to be thoroughly investigated for persistent pelvic pain potentially due to the lack of targeted curricula, including learning concepts. The aim of this study was to gain consensus on PSE learning concepts important for persistent pelvic pain according to expert clinicians.MethodsA three-round e-Delphi survey was conducted to generate and gain consensus on important PSE learning concepts for female persistent pelvic pain among 20 international, multidisciplinary expert clinicians (e.g., physiotherapists, gynaecologists, psychologists). Learning concepts generated by clinicians were rated by importance using a six-point Likert scale. Consensus on importance rating was considered reached for items with an IQR <1.0.ResultsThe expert clinicians generated 125 PSE learning concepts that were considered important for persistent pelvic pain; 92 (73.6%) learning concepts reached consensus on their importance rating. Of the 125 learning concepts, 102 were generated for persistent pelvic pain in general, and were categorised into 13 overarching PSE concepts (e.g., persistent pelvic pain involves changes to the brain and nervous system). Sixteen PSE concepts were generated for specific pelvic pain conditions (e.g., endometriosis) and seven concepts for specific life stages (e.g., adolescence).DiscussionThis study provides the first list of key PSE concepts tailored for persistent pelvic pain developed by expert clinicians. These concepts provide a framework for developing and implementing PSE curricula for persistent pelvic pain in research and clinical settings.